Crítica textual em Tutaméia terceiras estórias o prosseguir, a travessia ritmica - Paro, Sandra Regina (2008)
This work proposes a study of the work Tutaméia - Terceiras estórias, of João Guimarães Rosa through the Textual Critic, theory that allows to verify us the creative course of this book. Starting from the analysis of manuscripts and datiloscripts of the short story "No Prosseguir", in the attempt of establishing the difference among them in way to weave an approach of critical character of the work and starting from the publication of the story in the newspaper medical Pulso, of the construction paratextual of the work and of the first edition, of 1967, our objective is to draw, in agreement with the elements verified in the analysis, the path of the text in search of the expressiveness marked through the rhythm. We accomplished, in this work, a study of the tradition written for the composition of the book as accessory object to understand it as essential object. Historically, we passed of the relationship among the original, manuscript or printed paper, verifying the tradition by hand written and the typographic, establishing a path of the textual critic to the current days. We verified the construction unusual paratextual admitted by Guimarães Rosa in the short stories of Terceiras estórias and the organization editorial of the work before the norms effective editorials. The confrontation among the documents was meticulous work and it addressed us for some curiosities about the textual construction in Tutaméia - Terceiras estórias. We located elements directors for the understanding of the construction complete of the work through the rhythm as critical element. This research is, therefore, the attempt of establishing the text due to the manuscripts, datiloscripts and first edition through the exam of the documents the comparison among all of the testimonies to point a verification of the rhythm in Guimarães Rosa s text.